Psycho-analysis as history : negation and freedom in Freud - Roth, Michael S., 1957- (Cornell University Press, 1987)
No detailed description available for ""Psycho-Analysis as History"".
Keywords: Freud, Sigmund, -- 1856-1939.; Freud, Sigmund, -- 1856-1939; Psychoanalysis.; Psychohistory.; Psychoanalysis -- history; Psychoanalytic Theory; Psychoanalysis; Psychanalyse.; Psychohistoire.; psychoanalysis.; psychohistory.; PSYCHOLOGY -- Movements -- Psychoanalysis.; Psychohistory; Psychoanalyse.; Theorieën.; Psychoanalysis -- Theories of Freud, Sigmund, 1856-1939